Prevalence and Predictors of Anxiety and Depressive Symptoms among Adult Patients with Atopic Dermatitis in Malaysia Tertiary Referral Hospital - Nur Hafidah Ishak; Chong Seng Choi; Normala Ibrahim; Firdaus Mukhtar; Umi Adzlin Silim (Malaysian Journal of Medicine and Health Sciences, 2023)
Introduction: Atopic dermatitis (AD) is not only a cosmetic nuisance but is also associated with a significant impact on mental health and quality of life. Psychological symptoms are highly related to poor treatment adherence and recovery, more comorbidities, and a significant overall socioeconomic burden. Identifying the factors associated with anxiety and depression among patients with AD is important to modify and reduce the risk of developing these psychiatric complications. Methods: This was correlational research conducted in the dermatology clinic of four hospitals in Klang Valley, namely Hospital Kuala Lumpur, Hospital Tengku Ampuan Rahimah Klang, Hospital Selayang, and Hospital Ampang. By using a purposive sampling method, 128 samples (n=128) of adult patients with AD aged 18-65 were included. A questionnaire was administered regarding sociodemographic background, illness characteristics of AD, the Investigator’s Global Assessment (IGA), Malay version of the Automatic Thought Questionnaire-17, GAD-7, and PHQ-9. Results: The prevalence of anxiety and depressive symptoms among adult patients with AD is 31.3% and 46.9% respectively. Multivariable logistic regression analysis revealed that age and personal maladjustment (PM) predict anxiety symptoms, while only negative self-concept/expectation (NSNE) predicts depressive symptoms. The hierarchical logistic regression model explained 51% (Nagelkerke’s R2) of the variance in anxiety symptoms and 56% (Nagelkerke’s R2) of depressive symptoms. Conclusion: There is a high proportion of anxiety and depressive symptoms among adult patients with AD which is associated with negative automatic thoughts. In the management of adult patients with AD, clinicians should consider mental health symptom screening and monitoring.